The influence of psycho-emotional stress in children of primary school age on the incidence of recurrent upper respiratory tract infections and the functional state of the myocardium - L.S. Ovcharenko; D.N. Sheludko; A.A. Vertegel (Zaslavsky O.Yu., 2017)
Background. Scientific and technical progress, intensification of educational process and information overload have a negative effect on unformed central nervous system of primary schoolchildren, causing stress, which affects the increase in the incidence of recurrent upper respiratory tract infections (URTI) and the functional state of the myocardium. In view of this, we analyzed a functional state of myocardium in children with recurrent URTI. The critical duration of the work of primary school child with electronic means of communication, which affects the quality of nighttime sleep and the nature of awakening in the morning, was established. We have studied the relationship of the above mentioned with the incidence of URTI, the level of school anxiety and functional reserve of the myocardium. The purpose of the study was to evaluate the functional reserve of the myocardium in children of primary school age, depending on the incidence of URTI and the level of psycho-emotional activity. Materials and methods. 239 children aged 6 to 9 years were examined. The analysis of the functional reserve of the myocardium was carried out in pupils with different incidence of the URTI, depending on the age. The influence of electronic communications on the quality of nighttime sleep and morning awakening was studied, and the level of school anxiety was evaluated. During the study, children were divided into two groups. Group 1 - children with recurrent acute respiratory diseases (n = 143). Group 2 - children who occasionally have URTI (n = 96). Results. Out of 239 children with recurrent acute respiratory infections, we have identified 173 children with reduced functional reserve of the myocardium (72.4 %). Among children with recurrent URTI, the incidence of reduced functional reserve of the myocardium was 76.2 %, and in occasionally ill children - 66.7 %. Children with recurrent URTI use electronic means of communication more often than occasionally ill children: a direct strong positive relationship was revealed between the decrease in the functional reserve of the myocardium and the time spent on gadgets as compared to children occasionally suffering from URTI. Conclusions. Children with recurrent URTI spend more time on electronic communication means than occasionally ill children. Among children with recurrent URTI, disturbances of night sleep and morning awakening are revealed most often. Children with recurrent URTI more often than occasionally ill children have high school anxiety. Prolonged use of electronic communication means, disturbances of night sleep and morning awakening are accompanied by a decrease of functional reserve of the myocardium.